2011
DOI: 10.1182/blood.v118.21.5312.5312
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand Factor, ADAMTS13 Activity, TNF-Alpha, and Their Relationships in Patients with Chronic Kidney Disease

Abstract: 5312 Patients with chronic kidney disease (CKD) have increased risks of endothelial dysfunction and thrombosis. Systemic inflammation may contribute to the endothelial dysfunction and accelerated thrombosis observed in CKD patients. von Willebrand factor (VWF), a well-known index of endothelial damage, has been reported to increase both in CKD and inflammatory states. ADAMTS13 is a specific VWF-cleaving protease, and some reports suggested that the ratio of VWF and ADAMTS13 maybe more useful in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Conversely, an increased plasma level of vWF is associated with cardiovascular diseases . Further, vWF regulates leukocyte extravasations during experimental peritonitis and other inflammatory diseases . We recently reported that multimeric vWF binds to NO synthase and inhibits insulin‐induced production of NO, thus promoting IR during hypoxia .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, an increased plasma level of vWF is associated with cardiovascular diseases . Further, vWF regulates leukocyte extravasations during experimental peritonitis and other inflammatory diseases . We recently reported that multimeric vWF binds to NO synthase and inhibits insulin‐induced production of NO, thus promoting IR during hypoxia .…”
Section: Introductionmentioning
confidence: 99%
“…VWF is a multimeric hemostatic protein that is released by both endothelial cells and platelets (Wagner, 1990;Sadler, 1998). Beside its role for platelet adhesion during hemostasis, VWF has become a relevant target in studies of the inflammatory response (Denis et al, 2001;Khan et al, 2012;Shen et al, 2012). Animal studies have shown that deficiency of VWF provides protection against ischemic stroke (Kleinschnitz et al, 2009) and atherosclerosis (Methia et al, 2001;van Galen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%